2016
DOI: 10.1007/s12664-016-0708-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma von Willebrand factor levels predict in-hospital survival in patients with acute-on-chronic liver failure

Abstract: vWF levels are markedly elevated, correlate with organ failure, and predict in-hospital survival in ACLF patients. This data provides a mechanistic basis for postulating that vWF-reducing treatments such as plasma exchange may benefit ACLF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 52 publications
4
26
1
Order By: Relevance
“…It has been shown that increased circulating vWF‐Ag levels are associated with increased mortality rates in patients with cirrhosis and in patients with liver damage attributed to hepatitis C infection . Moreover, patients with acute‐on‐chronic liver failure were found to have elevated levels of vWF‐Ag compared to healthy controls, but also compared to patients with cirrhosis, and vWF‐Ag levels were a valid tool to predict in‐hospital mortality in these patients . In addition, multiple studies have reported that reduced liver function and portal hypertension are associated with increased levels of circulating vWF‐Ag that might be released from activated endothelial cells as a response to increased shear stress .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that increased circulating vWF‐Ag levels are associated with increased mortality rates in patients with cirrhosis and in patients with liver damage attributed to hepatitis C infection . Moreover, patients with acute‐on‐chronic liver failure were found to have elevated levels of vWF‐Ag compared to healthy controls, but also compared to patients with cirrhosis, and vWF‐Ag levels were a valid tool to predict in‐hospital mortality in these patients . In addition, multiple studies have reported that reduced liver function and portal hypertension are associated with increased levels of circulating vWF‐Ag that might be released from activated endothelial cells as a response to increased shear stress .…”
mentioning
confidence: 99%
“…(8,10) Moreover, patients with acute-on-chronic liver failure were found to have elevated levels of vWF-Ag compared to healthy controls, but also compared to patients with cirrhosis, and vWF-Ag levels were a valid tool to predict in-hospital mortality in these patients. (11) In addition, multiple studies have reported that reduced liver function and portal hypertension are associated with increased levels of circulating vWF-Ag that might be released from activated endothelial cells as a response to increased shear stress. (5,8,12) However, the clinical relevance of vWF-Ag to assess preoperative liver function, and, concomitantly, predict postoperative clinical outcome post-LR, has not been evaluated so far.…”
mentioning
confidence: 99%
“…Plasma VWF levels are noted to be consistently higher in patients with acute-on-chronic liver failure (ACLF). 47,48 Prasanna et al, 49 in a study of 50 ACLF patients, showed that plasma VWF levels were 5-7-fold elevated, which correlated independently with organ failure and in-hospital survival. Similarly, in patients with cirrhosis and superimposed inflammation, VWF was high and predicted transplant-free survival.…”
Section: Emjmentioning
confidence: 98%
“…Plasma VWF levels are increased 2-3-fold in patients with chronic liver diseases (cirrhosis patients in the outpatient setting 39 and patients with noncirrhotic portal hypertension), 34,35 4.0-4.5-fold in patients with acute hepatic dysfunction (acute liver injury and acute liver failure), 46 and 5-7-fold in patients with ACLF. 39,49 This raises many questions on the reason this occurs; is it because of increased VWF production/secretion, reduced VWF clearance from the circulation, or both? Increased VWF secretion from endothelial cells may reflect endothelial activation.…”
Section: Why Are Plasma Von Willebrand Factor Levels Increased In Patients With Liver Failure?mentioning
confidence: 99%
“…42 Increased VWF activity has been associated with poor clinical outcomes in patients with acute-on-chronic liver failure. 43 Depletion of VWF in in vivo mice models of acute liver injury resulted in decreased liver fibrosis. 44 In contrast, ADAMTS13 (a disintegrin and metalloproteinase with thrombospondin type 1 motif, member 13), a VWF cleaving enzyme, is often decreased in cirrhosis.…”
Section: Mechanism Of Thrombosis and Role Of Doacs As Antifibrotic Agmentioning
confidence: 99%